2009
DOI: 10.1007/s11104-009-0126-7
|View full text |Cite
|
Sign up to set email alerts
|

Grazing-induced changes in plant species composition affect plant and soil properties of grassland mesocosms

Abstract: Grazing-induced floristic changes in plant communities may accelerate or reduce plant and soil processes through changes in litter quality. Here, we intended to elucidate if the joint action of live and senescing plant tissue of palatable and non-palatable species differentially influences soil processes and properties. We conducted a 1-year experiment with mesocosms from a subhumid grassland. Mesocosms were monocultures of palatable or non-palatable species and a multispecific control. Palatable species inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 73 publications
(93 reference statements)
1
31
0
1
Order By: Relevance
“…There is a range of potential indirect mechanisms through which soil carbon may be affected by increased grazing (Bardgett and Wardle 2003, De Deyn et al 2008, Semmartin et al 2010. Firstly, in the present study both RAB (P < 0.001, n = 120; Figure 3a) and root biomass (P < 0.001, n = 120; Figure 3b) were found to have a significantly positive correlation with SOC storage over three years, which suggests that the decrease of SOC storage with increased grazing can be attributed to grazing-induced decreases in plant biomass.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a range of potential indirect mechanisms through which soil carbon may be affected by increased grazing (Bardgett and Wardle 2003, De Deyn et al 2008, Semmartin et al 2010. Firstly, in the present study both RAB (P < 0.001, n = 120; Figure 3a) and root biomass (P < 0.001, n = 120; Figure 3b) were found to have a significantly positive correlation with SOC storage over three years, which suggests that the decrease of SOC storage with increased grazing can be attributed to grazing-induced decreases in plant biomass.…”
Section: Resultsmentioning
confidence: 99%
“…Grazing directly influences soil carbon dynamics and turnover by removing biomass but also returning carbon in the form of dung and urine deposition; trampling may also have direct effects (Bardgett and Wardle 2003). Grazing can also indirectly influence soil carbon storage in several ways (Bardgett and Wardle 2003, De Deyn et al 2008, Semmartin et al 2010. First, herbivores regulate the quantities of resources that are returned to the soil through changing biomass allocation patterns Wardle 2003, De Deyn et al 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Grazing can directly influence soil C stock dynamics by removing plant biomass and returning C through dung and urine input (Deng et al 2014a). Additionally, grazing can indirectly influence soil C stock from two aspects (Semmartin et al 2010). Firstly, livestock changes plant biomass allocation patterns and thus regulate much resources that are returned to the soil (De Deyn et al 2008); secondly, livestock changes plant species composition and thus alters soil C stock (Semmartin et al 2010), which demonstrated to impact on litter quality and decomposability (Bardgett and Wardle 2003).…”
mentioning
confidence: 99%
“…Additionally, grazing can indirectly influence soil C stock from two aspects (Semmartin et al 2010). Firstly, livestock changes plant biomass allocation patterns and thus regulate much resources that are returned to the soil (De Deyn et al 2008); secondly, livestock changes plant species composition and thus alters soil C stock (Semmartin et al 2010), which demonstrated to impact on litter quality and decomposability (Bardgett and Wardle 2003). Although mechanisms of the grazing effect on soil C stock were extensively studied in a wide range of ecosystems worldwide, little studies had examined the linkage between soil C stock and grazing-induced vegetation changes on the Loess Plateau.…”
mentioning
confidence: 99%